(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Diabetic foot ulcer (DFU) is one of the most difficult and severe effects of diabetes mellitus. It can lead to infection, hospitalization, and amputation. It is very important to properly examine and grade these ulcers in order to foresee how they will turn out and decide how to treat them. The Wagner and PEDIS systems are the most commonly utilized of the several classification systems. Aims: This study aims to evaluate the severity of diabetic foot ulcers using the Wagner and PEDIS scoring systems and to clinically correlate and compare the PEDIS and Wagner scoring systems with patient outcomes in cases of diabetic foot ulcers. Materials and Methods: A prospective observational study was conducted in the Department of General Surgery over a period of 12 months. A total of 70 patients diagnosed with DFUs were included after obtaining informed consent. Each patient underwent detailed clinical evaluation, laboratory investigations, and ulcer assessment using both the Wagner and PEDIS scoring systems. Patients were followed up throughout their hospital stay and during outpatient visits to monitor progress and final outcome. Statistical analysis was performed using SPSS software. Correlations between the two scoring systems and patient outcomes were analyzed using the Chi-square test and Pearson correlation coefficient. Results: Out of 70 patients with DFUs, 55 (78.57%) were men and 15 (21.43%) were women, and the average age was 57.42 years. The forefoot was the most prevalent place for an ulcer (38; 54.28%). According to the Wagner classification, 14 (20.00%) had Grade I ulcers, 21 (30.00%) had Grade II ulcers, 19 (27.14%) had Grade III ulcers, 13 (18.57%) had Grade IV ulcers, and 3 (4.29%) had Grade V ulcers. The PEDIS system said that 10 (14.28%) were Grade 1, 28 (40.00%) were Grade 2, 24 (34.28%) were Grade 3, and 8 (11.42%) were Grade 4. Higher Wagner and PEDIS grades were substantially correlated with worse outcomes, extended hospitalizations, and increased amputation rates (p < 0.001). Both grading systems accurately reflect ulcer severity and predict prognosis, according to a substantial positive correlation between them (r = 0.812, p < 0.001). Conclusion: The Wagner system is still a simple and quick way to use in the clinic, but the PEDIS system is better for making predictions and planning management because it includes infection and perfusion characteristics.